Ruang Lingkup Baru Studi Ekonomi Pembangunan Islam di Indonesia: Pendekatan Bibliometrik dan Systematic Literature Review - Afif, Rafiq Azzam Al; Rizki, Darlin; Mustikasari, Rohayani; Praditya, Rifqi (Jurnal Ilmiah Ekonomi Islam, 2024)
The decline of Islamic civilization and the rise of Western civilization caused economic stagnation in Islamic countries. To address this problem and establish a scientific framework separate from the secular perspective, Muslim scientists develop Islamization of science movement. Muslim scientists are pushing for the Islamization of development economics. But the literature on Islamic economic development has been highly constrained and challenging to develop due to the study's confinement to material objects. The study uses the bibliometric and systematic literature review (SLR) methods to obtain a much broader picture of the development of Islamic economic development study. In this case, the literature collected comes from the database of journals in the Google index. The results show that the trend of the study of Islamic economic development has been increasing, suggesting that for about a decade, the topic of Islamic development economic research has been favored by researchers in the field of economics. The results of the mapping with Vosviewer and by reviewing the selected journals indicated that the future scope of the study of Islamic development economics is based on publication trends in Islamic finance system development, Islamic sustainable development, Islamic human development, Muslim community-based development, and Islamic agriculture development.